The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
DOI: 10.33915/etd.1922
|View full text |Cite
|
Sign up to set email alerts
|

National survey of psychological practices across rural and urban communities

Abstract: The purpose of this study was to examine potential differences in the practice of psychology across urban and rural communities. The review of the rural literature suggests that psychologists in rural areas are likely to encounter numerous ethical dilemmas and problems that are related specifically to the characteristics of such communities. To date, however, much of this literature has been based on theory and the individual experiences of practitioners. This study sought to quantify any differences in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 79 publications
(233 reference statements)
0
3
0
Order By: Relevance
“…[22] As a result, non-community members are viewed with suspicion and distrusted making research in rural communities more difficult for outside institutions. [22] In 1991, Murray and Keller suggested that the urban model of mental health service delivery was inappropriate to meet the needs of rural communities [21] and we are suggesting the urban model for research studies follows suit.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…[22] As a result, non-community members are viewed with suspicion and distrusted making research in rural communities more difficult for outside institutions. [22] In 1991, Murray and Keller suggested that the urban model of mental health service delivery was inappropriate to meet the needs of rural communities [21] and we are suggesting the urban model for research studies follows suit.…”
Section: Discussionmentioning
confidence: 94%
“…However, the common model for research studies developed largely in urban-based areas with access to many resources. [21] In addition to resources, there may be public familiarity with the researchers, which may translate to trust. For many rural areas this approach would mean the only time participants are exposed to researchers are within the confines of the research study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation